Development of a Computerized System for Fabric Structure Design based on Dobby Device Mechanism - Elsideeg Ahmed, Yousif Elhadi; Omer Idris, Abdu Idris; Abdallah Idris, Fadl Elmoula (Gezira Journal of Engineering and Applied Sciences, 2009)
Generally,  a fabric design  can  be established as follows: firstly. The required fabric design is planned on the punched plastic card using the punching machine. Secondly, the punched plastic card  is used by the dobby device that  attached to the textile machine (rapier weaving loom) to make the final fabric design as required.      In this study, a direct interfacing system between a personal computer and the textile machine (rapier weaving loom) was established to replace the conventional system (plastic card and punching machine).           This  system  is  applied  in  the  University  of  Gezira to enhance performance (decrease the design time, requirements and the complexity) of the existing conventional dobby device. The  system  was   developed  using  Microsoft  Visual  Basic, Personal Computer, coil, and Parallel Printer Port. The system reads the machine statues via the input lines connected to the power adapter and a mechanical sensor. Then the system issues a suitable  action  on the machine by generating the electric signal applied  on  the  coil.     The magnetic field controls  the shaft movement and selects the required color according to the design parameters. The system also repeats the color selection process until the total length required is completed.By using this system; the  woven design operations  become quite  simple, easy  and flexible.